Rezim Keamanan Maritim dalam Penanganan Pembajakan Kapal di Selat Malaka - Riskey Oktavian (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2021)
Abstract This article describes the form and performance of the Malacca Straits Patrol (MSP) cooperation as a maritime security regime in dealing with maritime piracy in the Straits of Malacca in the year 2008-2020. It is explored and analyzed using a theoretical approach of maritime security regimes, with the concept of maritime piracy, and the concept of maritime security. The research method used is qualitative based on case study and descriptive analysis. Sources of data were obtained from interviews and documentation with validated through triangulation of data sources and negative case analysis. The results of the study found the maritime piracy in the Straits of Malacca led to the development of dynamic threat perspective between littoral states and non-littoral user states depending on the priority of each states maritime interests to the strategic value of the Malacca Strait. This prompted the establishment of the Malacca Straits Patrol (MSP) cooperation as a form of maritime security regime with a cooperative security mechanism that has principles, norms, rules, and decision-making procedures aimed at dealing with maritime piracy of Malacca Strait through four programs: (1) Malacca Straits Sea Patrol (MSSP); (2) Eyes in the Sky Combined Maritime Air Patrols (EiS-CMAP); (3) Malacca Straits Patrol Intelligence Exchange Group (MSP-IEG); and (4) the Malacca Straits Patrol Joint Coordination Committee (MSP-JCC). It has a low level of effectiveness performance as the output product of the regime make outcome changes in the collective behavior of Indonesia, Malaysia, Singapore, and Thailand that optimum comply with a few rules of the game in the implementation of the MSSP, EiS CMAP, MSP-IEG, and MSP-JCC programs, because hampered by lack of capability and mutual mistrust. The results of these performances made the operationalization of the MSP regime to minimum, resulting in the unresolved problem of maritime piracy of the Malacca Strait according to the objectives MSP regime. Recommends for extending MSP to Strait of Singapore; increased capability of MSSP and EiS-CMAP; review the transparency information exchange of MSP-IEG; and increasing awareness and financial support, equipment, and training from interested non-littoral actors to littoral actors to make MSP more effective in dealing with piracy in the Straits of Malacca. Keywords : Straits of Malacca; Maritime Piracy; Maritime Security; Malacca Straits Patrol; Maritime Security Regime